Distinct roles of the left and right prelimbic cortices in the modulation of ethanol consumption in male mice under acute and chronic social defeat stress - Canto-de-Souza, Lucas [UNESP]; Baptista-de-Souza, Daniela [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP]; Planeta, Cleopatra [UNESP] (Springer Nature, 2024)
Rationale: Chronic stress exposure disrupts the medial prefrontal cortex’s (mPFC) ability to regulate impulses, leading to the loss of control over alcohol drinking in rodents, emphasizing the critical role of this forebrain area in regulating alcohol consumption. Moreover, chronic stress exposure causes lateralization of mPFC functions with volumetric and functional changes, resulting in hyperactivity in the right hemisphere and functional decrease in the left. Objectives: This study investigated the inhibitory role of the left prelimbic cortex (LPrL) on ethanol consumption induced by chronic social defeat stress (SDS) in male mice and to examine if inactivation of the LPrL causes disinhibition of the right mPFC, leading to an increase in ethanol consumption. We also investigated the role of lateralization and neurochemical alterations in the mPFC related to ethanol consumption induced by chronic SDS. To this end, we examined the activation patterns of ΔFosB, VGLUT2, and GAD67 in the left and right mPFC. Results: Temporarily blocking the LPrL or right PrL (RPrL) cortices during acute SDS did not affect male mice’s voluntary ethanol consumption in male mice. When each cortex was blocked in mice previously exposed to chronic SDS, ethanol consumption also remained unaffected. However, male mice with LPrL lesions during chronic SDS showed an increase in voluntary ethanol consumption, which was associated with enhanced ΔFosB/VGLUT2-positive neurons within the RPrL cortex. Conclusions: The results suggest that the LPrL may play a role in inhibiting ethanol consumption induced by chronic SDS, while the RPrL may be involved in the disinhibition of ethanol consumption.
Keywords: Ethanol consumption; Lateralization; Medial prefrontal cortex; Mice; mPFC prelimbic cortex; PrL; Social defeat stress; Two-bottle choice; VGLUT2; ΔFosB